A RhoGAP venom protein from Microplitis mediator suppresses the cellular response of its host Helicoverpa armigera. (July 2020) - Du, Jie; Lin, Zhe; Volovych, Olga; Lu, Zhiqiang; Zou, Zhen
Abstract: Female parasitoid wasps normally inject virulence factors together with eggs into their host to counter host immunity defenses. A newly identified RhoGAP protein in the venom of Microplitis mediator compromises the cellular immunity of its host, Helicoverpa armigera . RhoGAP1 proteins entered H. armigera hemocytes, and the host cellular cytoskeleton was disrupted. Depletion of MmGAP1 by injection of dsRNA or antibody increased the wasp egg encapsulation rate. An immunoprecipitation assay of overexpressed MmGAP1 protein in a Helicoverpa cell line showed that MmGAP1 interacts with many cellular cytoskeleton associated proteins as well as Rho GTPases. A yeast two-hybrid and a pull-down assay demonstrated that MmGAP1 interacts with H. armigera RhoA and Cdc42. These results show that the RhoGAP protein in M. mediator can destroy the H. armigera hemocyte cellular cytoskeleton, restrain host cellular immune defense, and increase the probability of successful parasitism. Highlights: MmGAP1 is highly expressed in female parasitod wasp's venom apparatus. MmGAP1 can enter H. armigera hemocytes and disrupt host cellular cytoskeleton. MmGAP1 can affect host cellular immune response. MmGAP1 interacts with host RhoA and Cdc42 in vivo and in vitro.